S121 Efficacy of macitentan in a large, real life population of patients with pulmonary arterial hypertension. (December 2018) - Nashat, H; Barbosa, J; Harries, C; Price, L; McCabe, C; Kempny, A; Wort, SJ; Gatzoulis, MA; Dimopoulos, K
Abstract : Background: Pulmonary arterial hypertension (PAH), a rare and aggressive condition, can only be managed therapeutically with a limited selection of pulmonary vasodilators. Macitentan, the newest endothelin receptor antagonist (ERA), approved for PAH therapy is a more potent antagonist of the two endothelin receptors, than older ERAs, with significant improvement in morbidity/mortality endpoints in a large multicentre study, the SERAPHIN trial. Aim: To investigate the efficacy of macitentan in a real life population of patients with PAH in a large tertiary pulmonary hypertension centre. Methods: Patients commenced on macitentan between 2014 and 2017 were included. Clinical parameters, including 6 min walk distance (6 MWD), World Health Organisation functional class (WHO-FC), brain natriuretic peptide (BNP), quality of life scores and haemoglobin concentration, were measured before and after the initiation of macitentan. A subgroup underwent right heart catheterisation (RHC) before and at least >6 months after macitentan. Changes in mean pulmonary arterial pressure (mPAP), pulmonary vascular resistance (PVR) and cardiac output (CO) were recorded. Results: A total of 107 patients (78 female mean ages 51±16 years) were included. Thirty nine patients had PAH related to congenital heart disease, 23 had PAH related to connective tissue disease, 15 had PAH related to chronic thromboembolic disease (CTEPH), 27 had idiopathic PAH, 3 had porto-pulmonary hypertension. Significant improvements was seen in 6 MWD (300.86±126.56 m to 343.17±132.97 m, p=0.001). BNP and QoL scores, showed no significant improvement, p=0.18 and p=0.63 respectively. Haemoglobin levels remained stable, 157±31 g/L to 153±31 g/L, (p=0.13). Nineteen patients had RHC prior to and after macitentan introduction. Baseline hemodynamic parameters were as follows: mPAP 50±14 mmHg, PVR 12±6 WU, and CO 3.6±1.3 L/min. At follow up, significant improvements were observed in PVR, which reduced from 12±6 WU to 8±4 WU (p =0.017). The CO improved from 3.6±1.3 L/min to 4.34±1 L/min (p =0.06) and the mPAP reduced from 50±14 mmHg to 43±15 mmHg (p =0.16 ) Conclusions: Significant improvements were seen in exercise capacity, functional class and hemodynamic parameters with the use of macitentan in this real life population. Reference: Pulido T, Adzerikho I, Channick RN, et al. Macitentan and morbidity and mortality in pulmonary arterial hypertension. N Engl J Med2013;369(9):809–818.